Pelaksanaan Prinsip Efisiensi Sumber Daya dalam Green Economy oleh UMKM Kuliner dan Dampaknya pada Lingkungan - Afrida Rosa Marsela; Nurma Fitrianna (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research discusses the application of resource efficiency principles in the context of green economy by culinary Micro, Small and Medium Enterprises (MSMEs) and their impact on the environment. Green economy is an approach that aims to improve human welfare and social justice while reducing the risk of environmental damage and resource scarcity. In this study, the authors identify the challenges that MSMEs face in implementing green practices. Case examples from several MSMEs show that despite the commitment to implement the principles, there are still difficulties in sustainable management operations. This research aims to provide recommendations for improving the implementation of green economy in the culinary sector, so that MSMEs not only contribute to the economy but also preserve the environment.